NRF2/miR-140 signaling confers radioprotection to human lung fibroblasts. Issue 1 (1st December 2015) - Duru, Nadire; Gernapudi, Ramkishore; Zhang, Yongshu; Yao, Yuan; Lo, Pang-Kuo; Wolfson, Benjamin; Zhou, Qun
Highlights: Ionizing radiation induces BRCA1-dependent activation of NRF2 in human lung fibroblasts. BRCA1 activates NRF2 through the negative regulation of KEAP1. miR-140 is a novel target gene for NRF2 in human lung fibroblasts. BRCA1/NRF2/miR-140 signaling axis confers radioprotection to human lung fibroblasts. Abstract: Breast and lung cancer patients who are treated with radiotherapy often have severe side effects, including radiation-induced lung damage and secondary cancers. Activation of the NRF2 pathway is a well-known mechanism that protects cells against radiation induced oxidative stress, but its role in radiation-induced lung damage is not well understood. Using human lung fibroblasts (HLFs) we found that ionizing radiation (IR) leads to BRCA1-dependent activation of NRF2 through the inhibition of KEAP1 function, promoting the nuclear accumulation of NRF2, and activating critical radioprotective mechanisms. We discovered that NRF2 directly binds to the miR-140 promoter and increases its expression in response to IR treatment. Gain and loss of function studies further showed the ability of miR-140 to regulate lung fibroblast self-renewal upon irradiation, a potential mechanism to contribute to the regulation of DNA repair. We verified our in vitro findings using primary lung fibroblast cultures from wild type and Nrf2 (KO) mice. Using these models we showed that IR induces overexpression of Brca1, Nrf2 and miR-140 in lung tissue after irradiation. These data reveal a novel radioprotective mechanism in which IR promotes NRF2 nuclear translocation and subsequent activation of miR-140 transcription in HLFs.